Implementation and Effectiveness of Equalizing Echelon IV Structural Positions into Functional Positions at the Blitar Regency Culture and Tourism Service - Yayan Wahyuni; Abu Talkah; Deby Santyo Rusandy (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The Blitar Regency Personnel and Human Resources Development Agency has made a new innovation, namely by creating a system of adjustment/Inpassing procedures, carrying out competency tests and determining requirements for Adjustment/Inpassing which are further regulated by the Head of the Functional Position Development Agency. The aim of this research is to determine the implementation and effectiveness of equalizing echelon IV structural positions into functional positions at the Blitar Regency Culture and Tourism Service. This research method is qualitative research. The research location was carried out at the Blitar Regency Culture and Tourism Service in carrying out the functions and duties of the Blitar Regency Culture and Tourism Office. Research data is in the form of secondary and primary data. Primary data was obtained from components related to the implementation of the equalization of echelon IV positions into functional positions. Secondary data is data obtained from various sources within the Blitar Regency Culture and Tourism Service in the form of documents, journals, archival book records, the presence of Blitar Regency Culture and Tourism Service employees, this is adjusted to research needs. Data collection methods used in research are interviews, observation, documentation. This research's analytical method uses qualitative analysis. The results of this research are that equalizing structural positions to functional positions is like a tsunami storm that hits the ranks of Structural Administrator Officials. When the Minister of Administrative and Bureaucratic Reform Regulation Number 28 of 2019 concerning the Equalization of Administrative Positions into Functional Positions was implemented, it gave the impression that the Regional Government was just watching and waiting to take action. So after the deadline appeared on December 1 2021, with limited time, the Regional Government of Blitar Regency inevitably immediately processed the equalization of positions.